2014
DOI: 10.1200/jop.2013.001255
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoiesis-Stimulating Agent Use After Changes in Medicare Reimbursement Policies

Abstract: Purpose: Since 2004, concerns about the safety of erythropoiesis-stimulating agents (ESAs) have resulted in label changes and restrictions on their use. We examined changes in ESA use and blood transfusions over time. Methods Conclusion:Our study demonstrated a rapid decline in the percentage of patients treated with ESAs after changes to reimbursement policy, but not after warnings about use. Reimbursement restrictions of other overused or off-label drugs may help reduce health care expenditures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…2 We were thrilled that the authors confirmed our findings in patients with breast cancer using CancerLinQ. 2 We were thrilled that the authors confirmed our findings in patients with breast cancer using CancerLinQ.…”
mentioning
confidence: 52%
“…2 We were thrilled that the authors confirmed our findings in patients with breast cancer using CancerLinQ. 2 We were thrilled that the authors confirmed our findings in patients with breast cancer using CancerLinQ.…”
mentioning
confidence: 52%
“…16,17 Arneson et al, Hershman et al, and Li et al found that the use of ESAs had a 50%-57% reduction after the policy change based on claims. [18][19][20] Specifically, Li et al identified racial/ethnic and sex disparities in the impact of the policy change on the use of ESAs. 20 Before the reimbursement policy change, Medicare paid approximately $2 billion every year to reimburse for ESAs.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Some previous studies have examined the change in the use of ESAs and blood transfusions in cancer patients before and after the implementation of the Medicare reimbursement policy change. [32][33][34][35][36][37] Documented in the literature is a 26%-57% reduction in the use of ESAs after the policy change. [32][33][34][35] Results are mixed regarding the change in the use of blood transfusions.…”
Section: What This Study Addsmentioning
confidence: 99%
“…[32][33][34][35][36][37] Documented in the literature is a 26%-57% reduction in the use of ESAs after the policy change. [32][33][34][35] Results are mixed regarding the change in the use of blood transfusions. [32][33][34][35][36][37] These studies, however, lack control groups, which cast doubt on the validity of the study results.…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation